KAJIAN PENGEMBANGAN PRODUK SALAK SENASE (Salacca zalacca (Gaert.) Voss) BANGKALAN MADURA SEBAGAI PERMEN JELLY - Dedin Finatsiyatull Rosida; Arumsaka Arina Taqwa (JURNAL AGROTEKNOLOGI, 2019)
One various of candy, like jelly candy is made from fruit juice. Gel-forming material and the presence of acid, which has a certain elasticity texture. Jelly candy is a solid form with a relatively soft texture when chewed, elastic, made from sugar and other sweeteners with a mixture of fruit juice and gelling ingredients such as carrageenan or gelatin. Fruit juice from salacca contains various compounds that can act as antioxidants, including vitamin C and phenolic compounds and tannins. The purpose of this study was to determine the effect of carrageenan and gelatin on the quality of salacca jelly candy based on physical, chemical and organoleptic characteristic. This study used a completely randomized design with one factor with eight treatments, namely carrageenan and gelatin formulations. The formulation used was 2%: 0%; 4%: 0%; 2%: 15%; 4%: 15%; 2%: 18%; 4%: 18%; 0%: 15%; 0%: 18%. The best results of jelly candy treatment with carrageenan concentration of 2%. This resulted had moisture of 12.462%, ash of 0.597%, reducing sugar of 8.79%, total acid of 0.401%, pH of 4.76, gel strength of 36,706 N, color intensity of L 35.4; a* 8.3; b* 13.5. Based on organoleptic characteristic, its color value of 4.84 (rather like), aroma of 4.76 (rather like), texture of 4.76 (rather like) and flavor of 5.20 (like). Keywords: carrageenan, gel properties, gelatin, jelly candy, salacca